2009
DOI: 10.1209/0295-5075/87/48011
|View full text |Cite
|
Sign up to set email alerts
|

Swarming dynamics in bacterial colonies

Abstract: We determine and relate the characteristic velocity, length, and time scales for bacterial motion in swarming colonies of Paenibacillus dendritiformis growing on semi-solid agar substrates. The bacteria swim within a thin fluid layer, and they form long-lived jets and vortices. These coherent structures lead to anisotropy in velocity spatial correlations and to a two-step relaxation in velocity temporal correlations. The mean squared displacement of passive tracers exhibits a short-time regime with nearly ball… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
128
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(140 citation statements)
references
References 33 publications
8
128
0
1
Order By: Relevance
“…Thus, complex spatio-temporal patterns may emerge in interacting active particle systems. There are numerous experimental realizations of active matter, for example driven filaments on the molecular scale [6], colloidal systems [7,8], bacterial colonies [9][10][11][12][13][14][15][16][17] as well as macroscopic systems like flocking birds [18] and schooling fish [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, complex spatio-temporal patterns may emerge in interacting active particle systems. There are numerous experimental realizations of active matter, for example driven filaments on the molecular scale [6], colloidal systems [7,8], bacterial colonies [9][10][11][12][13][14][15][16][17] as well as macroscopic systems like flocking birds [18] and schooling fish [19].…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, the quantitative analysis of fascinating phenomena like clustering [11] and vortex formation [20] provide an a e-mail: grossmann@physik.hu-berlin.de b e-mail: pawelr@princeton.edu excellent opportunity to test theoretical predictions, and, on the other hand, experiments often reveal unforeseen novel phases of active matter. Recently, a number of experiments reported the emergence of dynamic vortex patterns in dense suspensions of Bacillus subtilis [12][13][14][15], Paenibacillus dendritiformis [16] as well as Escherichia coli [17]. In particular, it was observed that bacteria locally align their body axis.…”
Section: Introductionmentioning
confidence: 99%
“…Examples range from bacterial suspensions [8,9], spermatozoa [10,11], human crowds [12] to suspensions composed out of artificial self-propelled particles [13,14,15,16,17,18]. Such systems have frequently been studied in the last year in bulk focusing on clustering [19,20,21,22,23,24], swarming [25,26,27,28] and complex swirling or turbulence [29,30,31,32,33,34,35,36]. A static confinement has been shown to be able to stabilize these structures [37], accumulate and guide active particles [38,39,40,41,42,43].…”
Section: Introductionmentioning
confidence: 99%
“…We can thus for small enough ϵ approximate the solution by truncating the series at k = N , to obtain a system of 2N ODEs for θ 1 (t), ϕ 1 (t), ..., ϕ N (t), θ N (t). To capture the asymmetry in the film, we need to have at least N = 2, for which we start by assuming that λ 1 = 1, λ 2 = 4: this allows us to keep the contribution of θ 1 , ϕ 1 as the dominant one up to the order ϵ 4 , at which point θ 2 , ϕ 2 appear; the assumption we check to be consistent a posteriori.…”
Section: Boundary Conditionsmentioning
confidence: 99%